Cautivos del espejo de agua : signos de ritualidad alrededor del manantial Hueytlílatl, Los Reyes, Coyoacán - Declercq, Stan, 1970- (Ciudad de México : Bonilla Artigas Editores : Secretaría de Cultura, Instituto Nacional de Antropología e Historia, 2016)
"The present book analyzes the importance of the water springs within the Mesoamerican indigenous ritual and offers an interpretation of the archaeological context of some burials located next to a spring making use of a wide iconographic, historical and ethnographic repertoire. Much on inconography. This exhibition is based on the results of the archaeological excavation carried out between 2002 and 2003 in the Hueytlílatl spring, located in Los Reyes, Coyoacán, by the Archaeological Salvage Department of INAH - of which the author was a part - and of which Several objects of ceramic and lytic, several human burials and remains of architecture came to light, mostly belonging to the Late Postclassic and Early Colonial periods." (HKB Translation)--Page [9].
Introducción -- Una nueva historia de Coyoacán. Los Reyes y sus manantiales -- Signos de ritualidad : algunos antecedentes arqueológicos e históricos -- El contexto arqueológico -- Tlílatl, o el "agua negra" como entrada al mundo subterráneo -- Cautivos encerrados en el Monte Sagrado -- Palabras finales.
Incluye referencias bibliográficas (páginas 266-310) e índice.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Excavations (Archaeology) -- Mexico -- Coyoacán (Mexico City) -- Antiquities; Indians of Mexico -- Mexico -- Religion; Indians of Mexico -- Mexico -- Rites and ceremonies; Excavaciones (Arqueología) -- México -- Coyoacán (Ciudad de México) -- Antigüedades.; Indios de México -- México -- Religión.; Indios de México -- México -- Ritos y ceremonias; Coyoacán (Mexico City, Mexico) -- Antiquities; Coyoacán (Ciudad de México México) -- Antigüedades.; Libros electrónicos.